Cornerstone Allocation and IPO Underpricing - Non-Linear Evidence from the Swedish Market - Bodelind,Wictor; Sjöberg,Erik (2025)
This study investigates the relationship between cornerstone allocation and IPO underpricing in the Swedish market, as well as the moderating role of valuation uncertainty on this relationship. Employing OLS and 2SLS frameworks on a sample of 429 Swedish IPOs from 2010 to 2024, we find evidence of a causal non-linear relationship between cornerstone allocation and IPO underpricing, taking the form of an inverted U-shape. No evidence is found for valuation uncertainty having a moderating effect on this relationship. In light of these findings, we propose a framework of optimal cornerstone allocation, where different levels act as different signaling mechanisms.
Keywords: Cornerstone Allocation; IPO; Offer price; Underpricing; Valuation Uncertainty